MSME COMPETITIVE ADVANTAGES REVIEWED FROM ENTREPRENEURSHIP INSIGHT AND MARKET ORIENTATION ASPECTS WITH INNOVATION AS A MEDIUM - Julyanthry Julyanthry; Debi Eka Putri; Darwin Lie; Acai Sudirman (JURNAL MANAJEMEN DAN BISNIS, 2021)
Innovation and creativity in this digital era are needed in developing the business you want to do so that you don't get stuck in daily operational activities and pursue performance targets. Therefore, it takes a solid entrepreneurial spirit from within business actors to create innovation and creativity. In addition, the role of market orientation also plays a major role in providing broad market access so that the product innovations developed can reach end users. Thus, it is hoped that every business undertaken by business actors can survive and increase their competitive advantage. The urgency of this research is to examine the effect of entrepreneurship insight and market orientation on innovation and competitive advantage. On the other hand, This study also tries to confirm the mediating effect of innovation on the impact of entrepreneurship insight and market orientation on competitive advantage. This study uses a causal quantitative research design. The number of samples used in this study were 170 MSME business actors. The data analysis method used is Partial Least Square (PLS). The data analysis test tool uses statistical software Smartpls 3.0. This study concludes that the effect of entrepreneurship insight and market orientation on innovation is positive and significant. Likewise, the influence of entrepreneurship insight and innovation on competitive advantage obtained positive and significant results. On the other hand, the effect of market orientation on competitive advantage obtained positive but not significant results. This study also confirms that innovation can mediate the relationship between entrepreneurial insight and market orientation to competitive advantage.